Coffea canephora Bean Extract Induces NIH3T3 Cell Migration - Yessy Ariesanti; Ferry Sandra; Bianda Claresta; Livia Alvita (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Wound healing is an essential biological process that consists of sequential steps aimed at restoring the architecture and function of damaged cells and tissues. There are empirical evidences of using pure coffee bean powder as an alternative medicine in treating various types of wounds. However, there is limited data on coffee-induced wound healing, especially migration of cells. Therefore, current study was conducted to investigate the role of coffee extract in cell migration, especially fibroblast which is important for wound healing.METHODS: Coffea canephora beans were prepared, extracted and added in the NIH3T3 cell culture in final concentration of 2.5% and 5%. Then cytotoxicity test was performed using Na,30-[(phenylamino)-carbonyl]-3,4-tetrazolium]-bis(4-methoxy-6-nitro) benzenesulfonic acid hydrate (XTT) assay. Meanwhile, cell migration test was performed with scratch assay. All results were statistically analyzed.RESULTS: The 2.5% or 5% Coffea canephora beans extract (CCBE)-treated NIH3T3 cell numbers were almost similar with the numbers of NIH3T3 cells in starvation medium merely. Meanwhile, 2.5% and 5% CCBE showed significant decrease of the widths of scratched areas compared to starvation medium merely (ANOVA with LSD Post-hoc, p=0.000). After 24 h and 48 h, the average widths of 2.5% and 5% CCBE-treated scratched areas were 235.68±22.79, 50.36±5.29, 229.95±23.01, 27.68±2.83, respectively.CONCLUSION: Since both 2.5% and 5% CCBE are potential in inducing migration of fibroblast (NIH3T3 cell) and do not induce cytotoxicity, the CCBE could be potential as an agent for wound healing.KEYWORDS: coffee, Coffea canephora, NIH3T3, migration, cytotoxicity